2017
DOI: 10.1111/dom.12890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the long‐term cost‐effectiveness of liraglutide vs lixisenatide for treatment of type 2 diabetes mellitus in the UK setting

Abstract: Long-term projections suggest that treatment of patients with type 2 diabetes with liraglutide 1.8 mg is likely to be considered highly cost-effective compared with lixisenatide 20 µg treatment in the UK setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…A simple treatment algorithm which assumed that patients received once-weekly semaglutide or dulaglutide for 3 years was employed, as per previous long-term cost-effectiveness analyses of GLP-1 receptor agonists submitted to NICE and published in peer-reviewed journals. [32][33][34][35] This is also supported by data from general practice in the European Union big five markets, which reported a mean duration of treatment with GLP-1 receptor agonists of 29.35 months, rounded to 3 years, as treatment switching can occur only at the end of an annual cycle in the CDM. 36 After 3 years, treatment with once-weekly semaglutide or dulaglutide was discontinued and patients were assumed to intensify to basal insulin therapy with the most commonly used basal insulin analogue available in the UK, insulin glargine, with the cost of the least expensive, biosimilar version of insulin glargine applied (Abasaglar).…”
Section: Treatment Switching and Long-term Parameter Progressionmentioning
confidence: 57%
See 1 more Smart Citation
“…A simple treatment algorithm which assumed that patients received once-weekly semaglutide or dulaglutide for 3 years was employed, as per previous long-term cost-effectiveness analyses of GLP-1 receptor agonists submitted to NICE and published in peer-reviewed journals. [32][33][34][35] This is also supported by data from general practice in the European Union big five markets, which reported a mean duration of treatment with GLP-1 receptor agonists of 29.35 months, rounded to 3 years, as treatment switching can occur only at the end of an annual cycle in the CDM. 36 After 3 years, treatment with once-weekly semaglutide or dulaglutide was discontinued and patients were assumed to intensify to basal insulin therapy with the most commonly used basal insulin analogue available in the UK, insulin glargine, with the cost of the least expensive, biosimilar version of insulin glargine applied (Abasaglar).…”
Section: Treatment Switching and Long-term Parameter Progressionmentioning
confidence: 57%
“…A simple treatment algorithm which assumed that patients received once‐weekly semaglutide or dulaglutide for 3 years was employed, as per previous long‐term cost‐effectiveness analyses of GLP‐1 receptor agonists submitted to NICE and published in peer‐reviewed journals . This is also supported by data from general practice in the European Union big five markets, which reported a mean duration of treatment with GLP‐1 receptor agonists of 29.35 months, rounded to 3 years, as treatment switching can occur only at the end of an annual cycle in the CDM .…”
Section: Methodsmentioning
confidence: 99%
“…Empagliflozin and canagliflozin have both demonstrated cost-effectiveness vs. comparators in the UK [62][63][64]. Several studies of liraglutide in the UK have also concluded costeffectiveness, despite increased acquisition cost, due to reduction in diabetes-related complications [65][66][67]. However, cost-effectiveness analyses evaluate drugs as glucoselowering entities, and modelling is therefore based on traditional risk equations [68][69][70][71], which do not capture potential cardiovascular benefits [72].…”
Section: Therapy Choices Based On Cost-effectiveness Analysesmentioning
confidence: 99%
“…Costs of NPH insulin or insulin glargine, needles, metformin and daily self‐monitoring of blood glucose testing were captured following intensification. Costs of treating diabetes‐related complications were identified through literature review and were inflated to 2016 values using the Hospital and Community Health Services price index, where applicable . The impact of diabetes‐related complications on quality of life was captured by applying event disutilities in the year in which a complication occurred and, where appropriate, health state utilities for each subsequent year after the complication.…”
Section: Methodsmentioning
confidence: 99%